2015
DOI: 10.1016/j.chb.2015.04.075
|View full text |Cite
|
Sign up to set email alerts
|

A study of users’ experiences and beliefs about software update messages

Abstract: Prior studies report that computer users are often confused by software update messages. This study complements prior efforts by examining the relationship between self-reported ratings of specific software types and users selfreported measure of confusion, annoyance, and message noticeability for different software types using data gathered via two surveys (N1=78, N2=172) from anonymous computer users. The survey results showed that participants are commonly hesitant to apply updates, even though they report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…In a survey of 155 users, Fagan et al [9] explored software update notifications and found design features that led to annoying and confusing messages. Mathur et al [18] interviewed 30 users and found they felt annoyed with notifications that interrupted their tasks, including having to restart their machines.…”
Section: Related Workmentioning
confidence: 99%
“…In a survey of 155 users, Fagan et al [9] explored software update notifications and found design features that led to annoying and confusing messages. Mathur et al [18] interviewed 30 users and found they felt annoyed with notifications that interrupted their tasks, including having to restart their machines.…”
Section: Related Workmentioning
confidence: 99%
“…Das et al showed that social influences were key in users' consideration of security decisions and impactful towards security outcomes [20]. Several studies have identified the importance of individual considerations in the decision of users to apply a software update [21][22][23][24]. In particular, past experiences were identified to be an important factor in users' decisions, particularly if past experiences were negative [22,23].…”
Section: Related Workmentioning
confidence: 99%
“…Generally, software patches also invoke this type of power dynamic. Various empirical studies show that non-expert software users are reluctant to install patches themselves and that they are generally annoyed by update warnings (Fagan et al, 2015;Vaniea et al, 2014). The fact alone of needing to update and thus to abandon established user habits in order to keep using a game or a service can create unrest.…”
Section: Power Dynamicsmentioning
confidence: 99%